Patches in a timeline with ossia score - Celerier, Jean-Michaël (Revista Vórtex, 2021)
Handling of time and scores in patchers such as PureData, Max/MSP has been an ongoing concern for composers and users of such software. We introduce an integration of PureData inside the ossia score interactive and intermedia sequencer, based on libpd. This integration allows to score precisely event that are being sent to a PureData patch, and process the result of the patch's computations afterwards in score. This paper describes the way this integration has been achieved, and how it enables composers to easily add a temporal dimension to a set of patches, by leveraging both the computational power of PureData and the temporal semantics of the ossia system, in order to create complex compositions.